The association between depression symptoms, psychological burden caused by Covid-19 and physical activity: An investigation in Germany, Italy, Russia, and Spain - Brailovskaia, J.; Cosci, F.; Mansueto, G.; Miragall, M.; Herrero, R.; Bañosc, R. M.; Krasavtseva, Y.; Kochetkov, Y.; Margraf, J. (Psychiatry Research, 2020)
The outbreak of Covid-19 required the re-organization of everyday life. While some people accepted this challenge, other experienced the current situation as a heavy burden that impedes the adaptation to the new life conditions. The present study investigated factors that can impact the level of burden caused by Covid-19. Burden, depression symptoms and frequency of physical activity (e.g., jogging, cycling) were assessed via online surveys in overall 1,931 people from four countries (Germany: N = 625; Italy: N = 936; Russia: N = 230; Spain: N = 140). Similar result patterns were found in all country-specific samples. Burden by Covid-19 was significantly positively associated with depression symptoms, while it was significantly negatively linked to physical activity. Moreover, physical activity buffered the association between depression symptoms and burden. The present cross-national findings emphasize the protective effect of physical activity specifically in times of Covid-19. This issue should be addressed in governmental programs to longitudinally protect mental and physical health and to enhance the willingness to adhere to the anti-Covid-19 measures among the population.